Dominance of Vaccine‐Specific Chlamydia pecorum ompA Genotypes in Koalas From North‐Eastern Australia - Derek S. Sarovich; Martina Jelocnik; Praphaporn Stewart; Nina M. Pollak; Jessie S. F. Wong; Charlotte Kunesh; Chioma Ojiako; Jon Hanger; Amber Gillett; Ludovica Valenza; Timothy Portas; Jodie Wakeman; et al. (Ecology and Evolution)
ABSTRACT Chlamydia pecorum is a significant cause of morbidity and mortality in koalas and a major contributor to population decline. Due to its crucial role in vaccine development and use as a strain typing tool, multiple studies have investigated the prevalence and diversity of the C. pecorum outer membrane protein A (MOMP), encoded by ompA. This prior work has shown that ompA genotypes vary across geographical regions, with multiple genotypes identified across Eastern Australia. Despite these earlier studies, our understanding of the diversity and distribution of MOMP remains incomplete. Here, we aimed to assess the geographical distribution, diversity, and temporal stability of the C. pecorum ompA across wild koalas infected with Chlamydia in north‐eastern Australia. Full‐length ompA sequences were generated from 226 samples collected from 173 unique animals from multiple koala populations over a 4‐year time span. C. pecorum ompA genotypes F and G were the most common and were identified across all geographical regions. Genotype A was the next most common but mostly restricted to the South Brisbane region. In addition to two novel genotypes, rare genotypes, including livestock‐associated types E58 and L1, and koala‐associated H and I were sporadically identified. Comparison with historical ompA genotypes showed that the distribution of genotypes has remained stable over the past decade, suggesting limited selective pressure despite ongoing vaccination trials and management programmes. The stability of genotypes coupled with the identification of novel and livestock‐associated genotypes underscores the importance of continued surveillance to inform future vaccine development and conservation strategies for koalas.